Dataset: Mapping the Landscape of Cyber Law and Cyber-Harassment Research: A Comprehensive Data Analysis - Nur Riska Salsabila; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This data article presents a comprehensive analysis of cyber law and cyber-harassment-related journal articles within the field of law. The data was collected using the lens.org platform, employing keyword searches for